Pengaruh Opini Audit Sebelumnya, Disclosure, Debt default, Struktur Kepemilikan dan Pertumbuhan Perusahaan terhadap Opini Audit Going Concern - Rohmah, Rizqi Nur; Trisnawati, Rina (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study aims to analyze various factors that influence going concern audit opinion such as previous audit opinion, disclosure, debt default, ownership structure and company growth. This study uses samples from manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023 through a purposive sampling method, obtained a sample of 36 companies so that the research data amounted to 144 data. Data were collected using the documentation method sourced from financial statements and annual reports of companies accessed on the IDX website and the company website. This research is a quantitative study with logistic regression analysis. The results of the study show that previous audit opinions affect going concern audit opinions, while disclosure, debt default, ownership structure and company growth do not affect going concern audit opinions.